DEVELOPMENT COMPUTATIONAL THINKING TEACHING MATERIALS BASED CS UNPLUGGED FOR FRACTIONAL NUMBERS IN GRADE V ELEMENTARY SCHOOL - Shakinah, Jessy Permata; Lidinillah, Dindin Abdul Muiz; Apriani, Ika Fitri (EMTEKA: Jurnal Pendidikan Matematika, 2025)
Computational thinking is one of the essential skills in 21st-century learning. However, its implementation in elementary schools remains limited, mainly due to the lack of appropriate and contextual teaching materials. This study aims to develop CS Unplugged-based teaching materials that integrate informatics and mathematics learning, particularly in the topic of fractions. The research employed the Educational Design Research (EDR) method, which consists of three stages: (1) analysis and exploration, (2) design and construction, and (3) evaluation and reflection. The developed teaching materials were validated by four experts: an informatics expert, a mathematics expert, a learning design expert, and a pedagogical expert. The validation results indicated that the teaching materials were highly feasible, with an average percentage score of 87%. Therefore, the CS Unplugged-based teaching materials are considered suitable for use in elementary schools and can serve as an alternative solution to foster students' computational thinking skills, especially in schools with limited computer facilities. Berpikir komputasional merupakan salah satu keterampilan esensial dalam pembelajaran abad ke-21. Namun, implementasinya di sekolah dasar masih menghadapi tantangan, terutama karena terbatasnya bahan ajar yang relevan dan sesuai dengan konteks pembelajaran. Penelitian ini bertujuan untuk mengembangkan bahan ajar berpikir komputasional tipe CS Unplugged yang mengintegrasikan mata pelajaran informatika dan matematika, khususnya pada materi bilangan pecahan. Penelitian ini menggunakan metode Educational Design Research (EDR) yang terdiri atas tiga tahap, yaitu: 1) analisis dan eksplorasi, 2) desain dan konstruksi, serta 3) evaluasi dan refleksi. Produk bahan ajar yang dikembangkan divalidasi oleh empat ahli, yakni ahli informatika, ahli matematika, ahli desain pembelajaran, dan ahli pedagogik. Hasil validasi menunjukkan bahwa bahan ajar memiliki tingkat kelayakan yang sangat baik dengan rata-rata persentase sebesar 87%. Dengan demikian, bahan ajar ini layak digunakan di sekolah dasar dan dapat menjadi alternatif solusi dalam mengembangkan keterampilan berpikir komputasional peserta didik, khususnya di sekolah yang belum memiliki fasilitas komputer memadai.